Lithium ion battery
By using the AB ion distribution of different compound valences in the positive electrode material of lithium-ion battery, the problem of difficult to take into account both the side reaction and charging performance of lithium-ion batteries at high temperatures is improved, and The battery safety and charging performance are provided.
Patent Information
- Application Number
- CN202411273039.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
AI Technical Summary
The side reactions of the positive and negative electrode surfaces of lithium-ion batteries at high temperatures lead to the risk of thermal runaway control, and existing protective measures increase impedance and reduce lithium dendrites, which affects the safety and life of the battery, making it difficult to take into account both safety and charging capabilities.
Using the core body and surface structure of the positive electrode material, a semiconductor diode structure is formed through the distribution of AB ion at different valences, controlling the transmission resistance of lithium ions, combining carbonate and halogenated carbonate in the electrolyte to form a stable solvated structure, and regulating lithium Ion ejection and embedding speed.
It improves the structural stability and safety performance of the battery, reduces the lithium ion transmission speed, reduces the risk of negative electrode lithium extraction, and improves the low-temperature discharge capacity and normal temperature high-speed charging performance.
Smart Images

Figure BDA0005039300590000101 
Figure BDA0005039300590000102 
Figure BDA0005039300590000111
Abstract
Description
Technical Field
[0001] The present invention relates to the field of secondary batteries, and in particular to a lithium ion battery. Background Art
[0002] The safety performance of lithium-ion batteries is an important performance indicator. At high temperatures, the positive and negative electrode surfaces react with the electrolyte, generating heat and causing the risk of thermal runaway. The commonly used solution strategy is to use negative electrode film-forming materials to form a protective film on the negative electrode surface, or to use positive electrode protective additives such as nitrile to protect the positive electrode surface and reduce the side reactions. However, this process often increases impedance, resulting in a decrease in the rate of negative electrode lithium insertion.
[0003] At this time, lithium dendrites will be generated. The formation of lithium dendrites increases the risk of battery short circuit and thermal runaway, seriously affecting the safety and life of the battery. Therefore, in order to avoid this risk, it is necessary to reduce the rate of lithium ion extraction from the positive electrode to match the rate of lithium insertion at the negative electrode.
[0004] At present, there is a contradiction between these two requirements: on the one hand, it is necessary to protect the positive and negative electrode materials to reduce side reactions at high temperatures and improve safety performance. This process often leads to a planned increase in deterioration of charging capacity. On the other hand, it is necessary to improve charging capacity to meet the high-rate charging and discharging requirements of the battery. The core of this technical challenge lies in how to balance the protection of the positive and negative electrodes and the control of the migration rate of lithium ions.
[0005] In view of this, it is indeed necessary to provide a technical solution to the above problems. Summary of the invention
[0006] One of the purposes of the present invention is to provide a lithium ion battery to address the deficiencies of the prior art, so as to improve the problem that the current lithium battery is difficult to balance in terms of safety and high-rate charging.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A lithium-ion battery, comprising a positive electrode sheet and an electrolyte, wherein the positive electrode material of the positive electrode sheet comprises a core body and a surface layer located on the surface of the core body; wherein the core body comprises a chemical formula of LiaMO b The main material is a, a has a value range of 1 to 3, b has a value range of 1 to 3, M is at least one of transition metal ions, and the valence state of the M ion is +X; the surface layer contains A ions, and the valence state of the A ions is +Y; the core contains B ions, and the valence state of the B ions is +Z; wherein both A and B are at least one of the main group or subgroup elements of IA to IVA; and X, Y, and Z satisfy the relationship: 1<Z<X≤Y;
[0009] The electrolyte includes a lithium salt and a carbonate solvent, the carbonate solvent includes at least one of a carbonate and a halogenated carbonate, the concentration of the lithium salt in the electrolyte is E mol / L, the total concentration of the carbonate solvent in the electrolyte is F mol / L, and the concentration of each carbonate solvent in the electrolyte is Fn mol / L, wherein 0.8≤E≤1.2, E≤F≤5E, and Fn≤3E.
[0010] Preferably, the lithium salt includes at least one of LiPF6, LiBOB, LiBF4, LiTFSI, LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2.
[0011] Preferably, the carbonate solvent includes at least one of PC, EC, DFC, DMC, FEC, CEC, EMC, MF, MA, EA, and MP.
[0012] The present invention uses Li a MO b As the main material, by controlling the radial distribution of AB ions of different valences in the positive electrode material, an NP structure similar to a semiconductor diode is formed. The surface layer of the positive electrode material contains high-valence A ions, and the inner layer contains low-valence B ions. By utilizing the characteristics of large repulsion of A ions and small repulsion of B ions, the positive electrode material particles form a structure with large surface lithium ion transmission resistance and small inner lithium ion transmission resistance. In this way, when charging, lithium ions escape from the inside of the positive electrode material particles to the outside, and need to move from the inner layer with smaller repulsion to the surface layer with larger repulsion, which will encounter corresponding resistance, which can reduce the upper limit of the outward transmission speed of lithium ions, thereby reducing the risk of negative electrode lithium precipitation. During low-temperature discharge, lithium ions are embedded inward from the surface of the positive electrode material particles, and need to move from the surface layer with larger repulsion to the inner layer with smaller repulsion, and their transmission speed can be improved, thereby improving the low-temperature discharge capacity of the battery. At the same time, in combination with the electrolyte, the carbonates and halogenated carbonates therein can form an anionic solvation structure for LiPF6, forming a stable solvation structure in the proportion specified by the present invention, which can reduce side reactions at high temperatures and improve safety performance.
[0013] Preferably, based on the mass of the main material, the mass content of the M ions is ≥10%. Preferably, the weight proportion of the A ions in the surface layer is ≥200ppm; and / or, the interval extending 1μm from the surface of the core body toward its center is defined as the inner layer, and the weight proportion of the B ions in the inner layer is ≥200ppm. If the content of A ions in the surface layer is too low, the effect of reducing the lithium ion transmission speed cannot be achieved. Similarly, if the content of B ions in the core body is too low, the effect of increasing the lithium ion transmission speed cannot be achieved. By adopting the content parameters defined above in the present invention, the technical effect of simultaneously improving the electrode lithium precipitation and low-temperature discharge capacity can be achieved.
[0014] On the surface of the positive electrode material, the valence state of the A ion needs to be ≥ that of the M ion to achieve the effect of reducing the lithium ion transmission speed, and the effect is more obvious when the weight ratio of the A ion in the surface layer is ≥200ppm, and there is no effect when the content is lower. Inside the positive electrode, the valence state of the B ion needs to be ≤ that of the M ion to achieve the effect of promoting the lithium ion transmission speed, and the effect is more obvious when the weight ratio of the B ion in the inner layer is ≥200ppm. Lithium ions are inhibited by A ions when they are transmitted to the surface, and promoted by B ions when they are transmitted to the interior. The simultaneous presence of the two ions can achieve the effect of regulating the lithium ion extraction and embedding speed, thereby improving the room temperature high-rate charging performance and low-temperature discharge capacity of lithium batteries.
[0015] In some embodiments, the surface layer may also contain B ions appropriately, but in order to ensure that the surface layer inhibits the lithium ion transmission rate, the content of B ions needs to be controlled. Based on the weight ratio of A ions in the surface layer being ≥200ppm, the weight ratio of B ions in the surface layer needs to be controlled at 0-100ppm. If it exceeds this range, it will seriously affect the lithium ion transmission inhibition effect of the surface layer. Similarly, the core body may also contain A ions appropriately, but in order to ensure that the core body enhances the lithium ion transmission rate, the content of A ions needs to be controlled. Based on the weight ratio of B ions in the inner layer being ≥200ppm, the weight ratio of A ions in the inner layer needs to be controlled at 0-100ppm. If it exceeds this range, it will seriously affect the lithium ion transmission promotion effect of the core body. Wherein, the preparation method of the positive electrode material comprises the following steps:
[0016] S1, mixing the main material preparation raw materials including the lithium source and the M element precursor, and then dispersing them in an organic solvent, adding the B element precursor for premixing, and vacuum drying the mixture;
[0017] S2, dividing the mixture in step S1 into two groups, a and b, and then sintering them respectively to obtain product a and product b;
[0018] S3, crushing the product a prepared in S2 into large particles of 5 to 50 μm, and crushing the product b into small particles of 0.5 to 10 μm;
[0019] S4, mixing the large particles and the small particles obtained in S3 in a mass ratio of (7-9):(1-3), adding the A element precursor, and stirring and mixing;
[0020] S5. The mixture obtained in S4 is subjected to secondary sintering, crushing, and cooling to obtain the positive electrode material.
[0021] Preferably, in step S1, the premixing speed is 200-400 r / min, and the premixing time is 4-8 h; the vacuum drying temperature is 60-100° C., and the drying time is 10-15 h.
[0022] Preferably, in step S2, the primary sintering temperature is 800-1200°C, the primary sintering of the mixture of group a adopts a two-stage sintering method and the sintering time is 12-14 hours, and the primary sintering time of the mixture of group b is 5.5-7.5 hours.
[0023] Preferably, the two-stage sintering method includes: first continuously heating the temperature to D1°C at a heating rate of V1°C / min, then sintering at D1°C±50°C for t1 time, then continuously heating the temperature to D2°C at a heating rate of V2°C / min, then sintering at D2°C±50°C for t2 time, and finally annealing at a cooling rate of V3°C / min, wherein V1>V2, V2=V3, D1<D2, and t1=t2.
[0024] Preferably, the stirring and mixing speed in step S4 is 1000-1400 rpm, and the stirring time is 5-8 hours.
[0025] Preferably, in step S5, the secondary sintering temperature is 600-800° C., and the sintering time is 8-12 hours.
[0026] Compared with the prior art, the beneficial effects of the present invention are as follows: in the lithium-ion battery provided by the present invention, the positive electrode material in the positive electrode sheet has AB ions of different valences distributed radially, forming a NP structure similar to a semiconductor diode, and having better structural stability, thermal stability and electrochemical performance. Among them, lithium ions are inhibited by A ions when transmitting to the surface of the positive electrode material, and are promoted by B ions when transmitting to the inside of the positive electrode material. The synergistic effect of the two ions can achieve the effect of regulating the release and embedding speed of lithium ions, thereby improving the room temperature high-rate charging performance and low-temperature discharge capacity of the battery. In combination with the electrolyte, carbonates and halogenated carbonates can form more stable PF6 with LiPF6. 5- The anion solvation structure reduces side reactions in high temperature environments, improves safety performance, and reduces polarization losses to the battery. DETAILED DESCRIPTION
[0027] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.
[0028] The terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0029] The present invention aims to provide a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode material of the positive electrode sheet comprises a core body and a surface layer located on the surface of the core body; wherein the core body comprises a chemical formula of LiaMO b The main material is a, a has a value range of 1 to 3, b has a value range of 1 to 3, M is at least one of the transition metal ions, and the valence state of the M ion is +X; the surface layer contains A ions, and the valence state of the A ions is +Y; the core contains B ions, and the valence state of the B ions is +Z; wherein both A and B are at least one of the main group or subgroup elements of IA to IVA; and X, Y, and Z satisfy the relationship: 1<Z<X≤Y. The electrolyte includes a lithium salt and a carbonate solvent, and the carbonate solvent includes at least one of carbonate and halogenated carbonate. The concentration of the lithium salt in the electrolyte is Emol / L, the total concentration of the carbonate solvent in the electrolyte is Fmol / L, and the concentration of each carbonate solvent in the electrolyte is Fn mol / L, wherein 0.8≤E≤1.2, E≤F≤5E, and Fn≤3E.
[0030] Among them, the specific value of the above a can be 1, 1.5, 2, 2.5, 3, and may include but are not limited to the values listed above; the specific value of the above b can be 1, 1.5, 2, 2.5, 3, and may include but are not limited to the values listed above.
[0031] The lithium salt includes at least one of LiPF6, LiBOB, LiBF4, LiTFSI, LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2, preferably LiPF6.
[0032] The carbonate solvent includes at least one of PC, EC, DFC, FEC, CEC, DMC, EMC, MF, MA, EA, and MP, and is preferably a mixed solvent of PC, EC, DFC, and FEC.
[0033] The inventors found that the IA~IVA main group or subgroup element ions with different positive valence states have an electrostatic repulsive effect on lithium ions, and the higher the valence state, the greater the electrostatic repulsion. The outer layer contains high-valence A ions with greater repulsion, while the inner layer contains low-valence B ions with less repulsion. The positive electrode material particles form a structure with large surface lithium ion transmission resistance and small inner lithium ion transmission resistance. In this way, when charging, lithium ions escape from the inside of the positive electrode material particles to the outside, and need to move from the inner layer with less repulsion to the surface layer with greater repulsion. They will encounter corresponding resistance, which can reduce the upper limit of the outward transmission speed of lithium ions, thereby reducing the risk of lithium precipitation at the negative electrode. During low-temperature discharge, lithium ions are embedded inward from the surface of the positive electrode material particles, and need to move from the surface layer with greater repulsion to the inner layer with less repulsion. Their transmission speed can be improved, thereby improving the low-temperature discharge capacity of the battery. In combination with the electrolyte, the carbonate and halogenated carbonate therein can form an anionic solvation structure for LiPF6, forming a stable solvation structure in the proportion specified by the present invention, which can reduce side reactions at high temperatures and improve safety performance.
[0034] In some embodiments, the method for preparing the positive electrode active material comprises the following steps:
[0035] S1, mixing the main material preparation raw materials including the lithium source and the M element precursor, and then dispersing them in an organic solvent, adding the B element precursor for premixing, and vacuum drying the mixture;
[0036] S2, dividing the mixture in step S1 into two groups, a and b, and then sintering them respectively to obtain product a and product b;
[0037] S3, crushing the product a and the product b prepared in S2 respectively to obtain large particles of product a and small particles of product b;
[0038] S4, mixing the large particles and the small particles obtained in S3 in a mass ratio of (7-9):(1-3), adding the A element precursor, and stirring and mixing;
[0039] S5. The mixture obtained in S4 is subjected to secondary sintering, crushing, and cooling to obtain the positive electrode material.
[0040] The positive electrode material prepared by the preparation method of the present invention has better structural stability, thermal stability and electrochemical performance. Among them, the coating material can effectively reduce the thermal expansion caused by the temperature increase during the lithium insertion and extraction process of the positive electrode material, and effectively reduce the mechanical attenuation of the coating layer, improve the interface stability of the positive electrode material, and at the same time play a good role in alleviating the decomposition of the electrolyte and the corrosion of the positive electrode material, so that the electrochemical performance of the positive electrode material under high voltage is improved.
[0041] In some embodiments, in step S1, the speed of the premix is 200-400 r / min, specifically 200 r / min, 210 r / min, 220 r / min, 230 r / min, 240 r / min, 250 r / min, 260 r / min, 270 r / min, 280 r / min, 290 r / min, 300 r / min, 310 r / min, 320 r / min, 330 r / min, 340 r / min, 350 r / min, 360 r / min, 370 r / min, 380 r / min min, 400r / min may include but are not limited to the values listed above; the premixing time is 4-8h, specifically 4h, 5h, 6h, 7h, 8h, and may include but are not limited to the values listed above; the vacuum drying temperature is 60-100℃, specifically 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, and may include but are not limited to the values listed above; the drying time is 10-15h, specifically 10h, 11h, 12h, 13h, 14h, 15h, and may include but are not limited to the values listed above.
[0042] In some embodiments, in step S2, the primary sintering temperature is 800-1200°C, and specifically can be 800°C, 850°C, 900°C, 950°C, 1000°C, 1050°C, 1100°C, 1150°C, 1200°C, and can include but are not limited to the values listed above. The primary sintering of the mixture of group a adopts a two-stage sintering method and the sintering time is 12-14h, and the primary sintering time of the mixture of group b is 5.5-7.5h.
[0043] Among them, the two-stage sintering method includes: first continuously heating the temperature to D1℃ at a heating rate of V1℃ / min, then sintering at D1℃±50℃ for t1 time, then continuously heating the temperature to D2℃ at a heating rate of V2℃ / min, then sintering at D2℃±50℃ for t2 time, and finally annealing at a cooling rate of V3℃ / min, wherein V1>V2, V2=V3, D1<D2, t1=t2.
[0044] In some embodiments, the stirring and mixing speed in step S4 is 1000-1400 rpm, specifically 1000 rpm, 1050 rpm, 1100 rpm, 1150 rpm, 1200 rpm, 1250 rpm, 1300 rpm, 1350 rpm, 1400 rpm, 1450 rpm, 1500 rpm, and may include but are not limited to the values listed above; the stirring time is 5-8 h.
[0045] In some embodiments, in step S5, the secondary sintering temperature is 600-800°C, specifically 600°C, 650°C, 700°C, 750°C, 800°C, and may include but are not limited to the values listed above; the sintering time is 8-12h, specifically 8h, 9h, 10h, 11h, 12h, and may include but are not limited to the values listed above. Under the premise of calcining in steps within the above calcination temperature range, the present invention regulates and controls from multiple aspects to ensure the radial distribution of A and B elements in the final surface layer and inner layer, effectively improving the lithium cobalt oxide positive electrode material to control the positive electrode radial structure to solve the problem of difficulty in balancing high-rate charging and low-temperature discharge capacity performance.
[0046] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific embodiments, but the embodiments of the present invention are not limited thereto.
[0047] Example 1
[0048] The preparation method of the positive electrode material is:
[0049] 1) Primary mixing: Li2CO3 and Co3O4 are mixed according to the Li:Co element stoichiometric ratio of 1.05:0.993. In order to compensate for the loss of lithium under high-temperature sintering, the lithium source is measured at an excess of 5%. Isopropanol is used as a dispersant and a B element precursor is added. The solid and liquid mixtures are premixed in an oblique mixer with a premixing mechanical speed of 300r / min and a mixing time of 6h. After premixing, the above materials are vacuum dried at 80°C overnight for 12h to volatilize the dispersant and water.
[0050] 2) Primary sintering: The premixed mixture is divided into two groups, a and b, and then transferred to a muffle furnace for sintering at 800-1200°C. Specifically, the mixture of group a is sintered in two stages: the temperature is continuously increased at a heating rate of 3°C / min for the first 3 hours, and then maintained at a temperature platform of 500-600°C for 2 hours. From the 5th to the 11th hour, the temperature is continuously increased at a heating rate of 1.5°C / min, and then maintained at a temperature platform of 1050±30°C for 2 hours. Finally, annealing is performed at a cooling rate of 1.5°C / min to obtain product a after primary sintering. The mixture of group b is sintered at 1000°C for 6 hours to obtain product b after primary sintering.
[0051] 3) Primary crushing: crush product a with a crusher at a medium crushing degree for 2 hours to obtain large particles; crush product b with a crusher at a medium crushing degree for 4 hours to obtain small particles.
[0052] 4) Secondary compounding material: large particles and small particles are mixed in a mass ratio of 8:2, element A precursor, 500 ppm Al2O3 and 800 ppm LiF (LiF acts as a coating flux) are added, and the mixture is transferred to a high-speed mixer at a stirring speed of 1000-1400 r / min for 6 hours.
[0053] 5) Secondary sintering: The mixture was transferred to a muffle furnace again, and the heating rate was set to 5°C / min until the temperature reached 750±30°C, and sintered for 10 hours, and then cooled at a cooling rate of 3°C / min until it cooled to room temperature to obtain a secondary sintered product.
[0054] 6) Secondary crushing: The secondary sintered product is crushed with a crusher, the crushing degree is selected to be medium, and the time is 4 hours to obtain the positive electrode material.
[0055] In this embodiment, the B element precursor is MgF2, and the A element precursor is TiO2.
[0056] Preparation of electrolyte: In a glove box filled with argon, the moisture content is less than 5ppm, the oxygen content is less than 5ppm, ethyl propionate (EP) and propyl propionate are mixed in a mass ratio of 1:1, and ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC) and fluoroethylene carbonate (FEC) are added in a concentration ratio of 1:1:0:0.5 to obtain an organic solvent, and lithium hexafluoroborate and 1wt% of 1,3-propane sultone are added to the organic solvent at a concentration of 1 mol / L and mixed evenly to obtain an electrolyte.
[0057] Preparation of the battery: The positive electrode sheet made of the above positive electrode material, the negative electrode sheet made of the graphite material and the polyethylene separator are wound into a bare battery cell, which is packaged with an aluminum-plastic film, vacuum dried at 80°C, and after the water content reaches the standard, the electrolyte is injected, packaged, and subjected to the processes of formation, liquid extraction, capacity separation, aging, etc. to prepare a lithium-ion battery.
[0058] Embodiment 2-7
[0059] The difference between Example 2-7 and Example 1 is only that the addition ratio of carbonate ester and halogenated carbonate ester in the electrolyte is different, as shown in Table 3 for details.
[0060] The rest is the same as that of Example 1 and will not be described in detail.
[0061] Comparative Examples 1-4
[0062] The difference between Comparative Examples 1-4 and Example 1 is only that the addition ratio of carbonate ester and halogenated carbonate ester in the electrolyte is different, as shown in Table 3 for details.
[0063] The rest is the same as that of Example 1 and will not be described in detail.
[0064] Comparative Examples 5-10
[0065] The difference between Comparative Examples 5-10 and Example 6 is that the matched positive electrode materials are different, as shown in Table 1 and Table 3 for details.
[0066] The rest is the same as Example 6 and will not be described in detail.
[0067] The positive electrode and electrolyte formulations of the above-mentioned Examples 1 to 7 and Comparative Examples 1 to 10 were sorted out as shown in Tables 1 to 3.
[0068] Table 1
[0069]
[0070] In Table 1, “ / ” represents that no relevant element is added.
[0071] Positive electrode A: No A or B element precursors are added during the preparation of the positive electrode material.
[0072] Positive electrode B: No B element precursor is added to the primary mixing material in the positive electrode material preparation process.
[0073] Positive electrode C: No A element precursor is added to the secondary mixing material in the positive electrode material preparation process.
[0074] Positive electrode D: In the primary mixing material of the positive electrode material preparation process, the precursor of element B, MgF2, is added, and in the secondary mixing material, the precursor of element A, TiO2, is added.
[0075] Positive electrode E: TiO2 is added to the primary mixed material for the preparation of the positive electrode material, and MgF2 is added to the secondary mixed material.
[0076] Positive electrode F: A and B element precursors are added simultaneously to the primary mixed material for preparing the positive electrode material, and A and B element precursors are not added to the secondary mixed material.
[0077] Positive electrode G: In the primary mixed material for preparing the positive electrode material, no A and B element precursors are added, and the A and B element precursors are added to the secondary mixed material at the same time.
[0078] After the prepared lithium-ion battery was disassembled and cleaned, the positive electrode was cut using CP, and the cross section was tested using SEM-EDS to test the AB element content on the surface and inside. The results are shown in Table 2:
[0079] Table 2
[0080]
[0081]
[0082] The relevant embodiments are shown in Table 3 below.
[0083] Table 3
[0084]
[0085] The above-mentioned Examples 1 to 7 and Comparative Examples 1 to 10 were subjected to performance tests. The test results are shown in Table 4 below.
[0086] 1. Charge the lithium-ion battery at a constant current of 0.5C to 4.48V, and then charge at a constant voltage to a current of 0.05C until fully charged. Place 3PCS batteries in an explosion-proof temperature chamber, heat to the target temperature at a rate of 5℃ / min, and maintain for 30 minutes, cool back to room temperature, and pass if there is no fire or explosion.
[0087] 2. Lithium deposition test: Charge the lithium-ion battery to 4.48V at XXC constant current, then charge at constant voltage to 0.05C until fully charged, then discharge at 0.7C constant current to 3.0V, this is one charge and discharge cycle. Repeat the charge and discharge for 20 cycles, charge at XXC constant current to 4.48V, then charge at constant voltage to 0.05C until fully charged, transfer the battery to the glove box for disassembly, separate the negative electrode sheet, and observe whether there is lithium dendrite formation on its surface.
[0088] Table 4
[0089]
[0090]
[0091] From the test results in Table 4, it can be seen that Examples 1 to 7 and Comparative Examples 1-4 adjusted the ratio of lithium salt and carbonate in the electrolyte. The embodiments within the scope of the present invention have better comprehensive effects in safety tests and lithium precipitation tests, and can effectively improve the safety performance and charging rate of lithium-ion batteries; while the comparative examples that do not meet the carbonate-lithium salt ratio relationship have relatively poor safety performance and are not easy to pass the safety performance test.
[0092] From Comparative Examples 5-10, it can be seen that different pole pieces also affect the charging capacity of the battery. Pole piece D has a better effect than other pole pieces and can effectively reduce the risk of lithium plating.
[0093] In summary, the present invention can effectively improve the safety performance and charging rate of lithium-ion batteries by adjusting the relationship between the electrolyte components and using the positive electrode sheet of the present invention. On the one hand, adjusting the electrolyte can form a more stable PF 5- The anion solvation structure reduces side reactions in high temperature environments, improves safety performance, and reduces polarization losses to the battery. On the other hand, controlling the surface and core ion distribution of the positive electrode material can control the lithium desorption rate of the positive electrode material and prevent lithium deposition caused by the mismatch between the lithium desorption and insertion rates of the positive and negative electrodes.
[0094] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.
Claims
1. A lithium ion battery, comprising a positive electrode and an electrolyte, characterized in that: The positive electrode material of the positive electrode sheet includes a core body and a surface layer located on the surface of the core body; wherein the core body includes a chemical formula of Li a MO b The main material of the present invention, a is in the range of 1 to 3, b is in the range of 1 to 3, M is at least one of the transition metal ions, and the valence state of the M ion is +X; The surface layer contains A ions, the valence state of the A ions is +Y; the core contains B ions, the valence state of the B ions is +Z; wherein both A and B are at least one of the main group or subgroup elements of IA to IVA; and X, Y, and Z satisfy the relationship: 1<Z<X≤Y; The electrolyte includes a lithium salt and a carbonate solvent, the carbonate solvent includes at least one of a carbonate and a halogenated carbonate, the concentration of the lithium salt in the electrolyte is E mol / L, the total concentration of the carbonate solvent in the electrolyte is F mol / L, and the concentration of each carbonate solvent in the electrolyte is Fn mol / L, wherein 0.8≤E≤1.2, E≤F≤5E, and Fn≤3E.
2. The lithium-ion battery according to claim 1, characterized in that The lithium salt includes at least one of LiPF6, LiBOB, LiBF4, LiTFSI, LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2.
3. The lithium-ion battery according to claim 1, characterized in that The carbonate solvent includes at least one of PC, EC, DFC, DMC, EMC, FEC, CEC, MF, MA, EA, and MP.
4. The lithium-ion battery according to claim 1, characterized in that: Based on the mass of the main material, the mass content of the M ions is ≥10%.
5. The lithium-ion battery according to claim 1, characterized in that: The weight proportion of the A ions in the surface layer is ≥200ppm; and / or, the interval extending 1μm from the surface of the core body toward its center is defined as the inner layer, and the weight proportion of the B ions in the inner layer is ≥200ppm.
6. The lithium ion battery according to claim 3, characterized in that: The weight proportion of B ions in the surface layer is 0 to 100 ppm; and / or the weight proportion of A ions in the inner layer is 0 to 100 ppm.
7. The lithium ion battery according to any one of claims 1 to 6, characterized in that: The method for preparing the positive electrode material comprises the following steps: S1, mixing the main material preparation raw materials including the lithium source and the M element precursor, then dispersing them in an organic solvent, adding the B element precursor for premixing, and vacuum drying the mixture; S2, dividing the mixture in step S1 into two groups, a and b, and then sintering them respectively to obtain product a and product b; S3, crushing the product a prepared in S2 into large particles of 5 to 50 μm, and crushing the product b into small particles of 0.5 to 10 μm; S4, mixing the large particles and small particles obtained in S3 in a mass ratio of (7-9):(1-3), adding the A element precursor, and stirring and mixing; S5. The mixture obtained in S4 is subjected to secondary sintering, crushing, and cooling to obtain the positive electrode material.
8. The lithium-ion battery according to claim 7, characterized in that: In step S1, the premixing speed is 200-400 r / min, and the premixing time is 4-8 hours; the vacuum drying temperature is 60-100° C., and the drying time is 10-15 hours.
9. The lithium-ion battery according to claim 7, characterized in that: In step S2, the primary sintering temperature is 800-1200°C, the primary sintering of the mixture of group a adopts a two-stage sintering method and the sintering time is 12-14 hours, and the primary sintering time of the mixture of group b is 5.5-7.5 hours; Preferably, the two-stage sintering method includes: first continuously heating the temperature to D1°C at a heating rate of V1°C / min, then sintering at D1°C±50°C for t1 time, then continuously heating the temperature to D2°C at a heating rate of V2°C / min, then sintering at D2°C±50°C for t2 time, and finally annealing at a cooling rate of V3°C / min, wherein V1>V2, V2=V3, D1<D2, and t1=t2.
10. The lithium ion battery according to claim 7, characterized in that: In step S5, the secondary sintering temperature is 600-800° C., and the sintering time is 8-12 hours.
